Expressed Emotion and Attributions in Parents With Schizophrenia - Gregg, Lynsey; Calam, Rachel; Drake, Richard J.; Wolfenden, Lauren (Frontiers in Psychiatry, 2021)
We examined expressed emotion (EE) and attributions in parents with schizophrenia and compared them to parents without serious mental illness (SMI) in order to better understand the emotional climate of families in which a parent has schizophrenia. Parenting practices and parental reports of child behaviour were also compared between the two groups. The relationship of EE to attributions was examined in each group separately. Relationships between parental mental health, EE and attributions were explored in the parents with schizophrenia only. The Camberwell Family Interview was used to determine both EE and attributions in 20 parents with schizophrenia and 20 parents without SMI. We found that more parents with schizophrenia were rated as high EE than those without (60% and 35% respectively) although this was not a statistically significant difference. Parents with schizophrenia demonstrated significantly more hostility and criticism toward their children than those without SMI and made more child-blaming attributions. Blame was associated with increased hostility, less warmth and fewer positive remarks. Parental warmth was related to greater parenting self-efficacy, less harsh parenting practises, better child behaviour and a more positive parent-child relationship. We conclude that EE and attributions are potential explanatory variables to be considered in the development of preventative and early intervention strategies for families with a parent with schizophrenia or psychosis. Blame and warmth are modifiable factors that could be targeted within family and parenting interventions.